Argentophilic nucleolus organizer region as a proliferation marker in cervical intraepithelial neoplasia grade 1 of the uterine cervix - Guerra, Fernando Andres (2014)
AIM: p16INK4a and argentophilic nucleolus organizer region (AgNOR) can be used as markers for progression of cervical intraepithelial neoplasia grade 1 (CIN1) of the uterine cervix. Our objective was to study the predictive value of the AgNOR technique as a progression marker of CIN1 and its correlation with p16INK4A. MATERIAL AND METHODS: One uterine cervix biopsy from each of 75 patients with diagnosis of CIN1 was selected. All of these patients underwent a second biopsy, and these were also used for the study. RESULTS: The second biopsies showed: regression (20 patients), persistent CIN1 (38 patients), progression to CIN2 (10 patients) and progression to CIN3 (seven patients). p16INK4A showed reactivity in 67 of the 75 first CIN1 biopsies: 12 of the 20 cases that cleared the lesions and the 55 cases with persistent or progressive lesions were positive for p16INK4a (specificity: 40%; sensitivity: 100%; positive predictive value [PPV]: 82%; negative predictive value [NPV]: 100%). Samples with AgNOR areas less than 3.0 μ(2) returned in all cases, but patients whose lesions persisted or progressed to CIN2/CIN3, showed AgNOR areas greater than 3.0 μ(2) in 50/55 cases (specificity: 100%; sensitivity: 91%; PPV: 100%; NPV: 80%). CONCLUSIONS: p16INK4a is expressed in a high percentage of returning lesions. AgNOR might be a better marker of proliferation of CIN1 than p16INK4a (PPV = 100%), which means that a value greater than 3.0 μ(2) indicates the persistence or progression of the lesion. As its NPV is 80%, a value of AgNOR area less than 3.0 μ(2) in CIN1 leaves a margin of doubt about the future behavior of the lesion.